A case of porokeratosis with a variety of morphological manifestations - Xiang Zhang; Weiwei Shi; Jun Wang; Ruzhi Zhang (Clinical Case Reports, 2024)
Key Clinical Message This case illustrates the clinical heterogeneity of porokeratosis (PK), with a patient presenting with both disseminated superficial actinic PK‐like facial lesions and PK of Mibelli‐like lesions on the buttocks and lower limbs. Ultraviolet exposure, infection, and immunosuppression may contribute to the manifestation of multiple clinical forms in a single patient. Close monitoring for potential malignant transformation is essential, particularly in elderly patients with long disease duration and a history of oncological conditions.